Prolonged Treatment Response to Pembrolizumab in a Patient with Pretreated Metastatic Colon Cancer and Lynch Syndrome - Matthew Keating; Lisa Giscombe; Toufic Tannous; Kevan Hartshorn (Case Reports in Oncological Medicine)
Pembrolizumab and other immunotherapies now play a prominent role in the treatment of metastatic colon cancer. Clinicians have achieved significant response rates even in heavily pretreated patients, particularly those with mismatched repair deficiencies. The endpoint of pembrolizumab treatment for patients who enjoy a strong response remains unclear. Herein, we present the case of a 33-year-old man with pretreated metastatic colon cancer and a prolonged treatment response of over three years to single-agent pembrolizumab even after treatment discontinuation in July 2018. Prior to pembrolizumab, he was found to have lung and liver metastases despite multiple lines of chemotherapy. With pembrolizumab, there was a persistent downtrend in CEA level and uptrend in weight. After nearly three years of pembrolizumab treatment from October 2015 through July 2018, PET scan showed no FDG-avid disease, and further treatment was placed on hold. He remains under surveillance, with CT scan in February 2019 again showing no evidence of local or metastatic disease. In patients whose treatment duration and disease course are not defined by toxicities/progressive disease but rather by sustained treatment responses, we propose that immunotherapy treatment duration be guided by close monitoring of CEA levels, weight, and clinical exams in addition to traditional imaging.